Continuous glucose monitoring system profile of women diagnosed as gestational diabetes mellitus by International Association of Diabetes and Pregnancy Study Groups criteria and labeled as normoglycemic by alternate criteria in early pregnancy. Issue 10 (21st June 2022) - Gupta, Yashdeep; Singh, Charandeep; Goyal, Alpesh; Mani, Kalaivani; Bharti, Juhi; Singhal, Seema; Kachhawa, Garima; Kulshrestha, Vidushi; Kumari, Rajesh; Mahey, Reeta; Sharma, Jai B; Malhotra, Neena; et al.
Abstract: Aims/Introduction: We aimed to evaluate and compare continuous glucose monitoring system (CGMS)‐based glycemic parameters in women in early pregnancy (<20 weeks of gestation) who were classified as: (i) gestational diabetes mellitus (GDM) by the International Association of Diabetes and Pregnancy Study Groups (IADPSG), but normoglycemia by alternate (UK National Institute for Health and Care Excellence, Canadian Diabetes Association and Diabetes in Pregnancy Study group of India) criteria; and (ii) normoglycemia by both (IADPSG and alternate) criteria. Material and Methods: In this cross‐sectional study, eligible women underwent standard 75‐g oral glucose tolerance test, followed by the placement of a CGMS. Glycemia‐related parameters were calculated using the standard approach for CGMS data in pregnancy. Results: We enrolled 96 women at 14.0 ± 3.2 weeks of gestation. Of the women diagnosed as GDM by IADPSG criteria, 34.2%, 26.3% and 44.7% were classified as normoglycemic by UK National Institute for Health and Care Excellence, Canadian Diabetes Association and Diabetes in Pregnancy Study group of India criteria, respectively. Mean 1‐h postprandial glucose and time above range were significantly higher in women who were GDM by IADPSG, but normoglycemia by Canadian Diabetes Association criteria, compared with women with normoglycemia using both criteria. Similarly, mean 1‐h postprandial glucose, 2‐h postprandial glucose, peak postprandial glucose, 1‐h postprandial glucose excursion and time above range were significantly higher in women who were not identified as GDM by the UK National Institute for Health and Care Excellence criteria. Finally, women missed by the Diabetes in Pregnancy Study group of India criteria had significantly higher mean 1‐h postprandial glucose, 2‐h postprandial glucose, peak postprandial glucose, postprandial glucose excursion, 24‐h glucose and time above range parameters. Conclusions: More than one‐quarter of women diagnosed as GDM by IADPSG criteria are not identified by alternate criteria. Such women are significantly different from normoglycemic women in terms of several CGMS‐based glycemic parameters of clinical significance.